Transcriptome Reprogramming of Tomato Orchestrate the Hormone Signaling Network of Systemic Resistance Induced by Chaetomium globosum - Singh, Jagmohan; Aggarwal, Rashmi; Bashyal, Bishnu Maya; Darshan, K.; Parmar, Pooja; Saharan, M. S.; Hussain, Zakir; Solanke, Amolkumar U. (Frontiers in Plant Science, 2021)
Chaetomium globosum is a potential biological control agent effective against various plant pathogens. Several reports are available on mycoparastism and antibiosis mechanisms of C. globosum against plant pathogenic fungi, whereas a few states induced resistance. The potential induced defense component of C. globosum (Cg-2) was evaluated against early blight disease of tomato and further, global RNA sequencing was performed to gain deep insight into its mechanism. The expression of marker genes of hormone signaling pathways such as PR1, PiII, PS, PAL, Le4 and GluB were analyzed by qRT-PCR to determine best time point for RNA sequencing. The transcriptome data revealed that 22473 DEGs were expressed in tomato at 12 hrs post Cg-2 inoculation as compared to control plants and among these 922 DEGS had a fold change of -2 to +2 with p<0.05. The KEGG pathway analysis revealed that most of the DEGs were belonging to metabolic pathways, biosynthesis of secondary metabolites, plant-pathogen interaction, chlorophyll metabolism and plant hormone signal transduction. GO analysis revealed that DEGs were enriched mainly related to binding activity (GO:0005488), catalytic activity (GO:0003824), metabolic process (GO:0008152), cellular process (GO:0009987), response to stimulus (GO:0050896), biological regulation (GO:0065007) and transcription regulator activity (GO:0140110). The gene modulations in hormone signaling transduction, phenylpropanoid biosynthesis and MPK signaling indicated the upregulation of genes in these pathways. The results revealed active participation of JA and SA signaling transduction pathways which further indicated the involvement of ISR and SAR in systemic resistance induced by Cg-2 in tomato.